The Sociological Determinants of Human Resources Disclosure in Nigeria - DABOR, Alexander O.; KIFORDU, Anthony A.; DABOR, Eyesan Leslie (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed at examining the determinants of human resources disclosure. Precisely, this work investigates the influence of company size, profitability, audit type and firm origin on human resources disclosure. The study employed a regression analysis using the ordinary least squares techniques. The study findings indicated that Human resource disclosure is negatively connected to Firm Size. The influence of Audit type on Human Resources Disclosure was observed to be negative. The effect of company Origin on Human Resources Disclosure was found to be positive. Finally, profitability is found to be positively related to Human Resource Disclosure. This study concluded that firm precise features stimulus the level of human resources disclosure. The study recommended that regulatory agencies should develop a Human Resources Disclosure framework that will focus considerably on utilizing firm interest.